An update on drug development for the treatment of metabolic (dysfunction) associated fatty liver disease: Progress and opportunities. (October 2021) - Pan, Ziyan; Fan, Jian-Gao; Eslam, Mohammed
Abstract: Despite the rising health burden of metabolic (dysfunction) associated fatty liver disease (MAFLD), there are no approved pharmacotherapies for MAFLD currently. This situation led to a significant escalation in drug development and randomized controlled trials for MAFLD, particularly as novel information about its molecular pathogenesis unfolds. Currently, there are numerous investigational candidate drugs for MAFLD in various stages of clinical development that act on different pathophysiological processes, such as metabolism/steatosis, inflammation or fibrosis. Here, we provide an update on drug development for the treatment of MAFLD and discuss the prospects and challenges for improving and accelerating the nonalcoholic fatty liver disease drug discovery pipeline.